Development and Comparative Evaluation of a Novel Aloe vera–Vinegar Gel as a Sustainable Histological Slide Coating Agent - Deepasakthi, Jayagopi; Sinduja, Palati (Journal of Dentistry Indonesia, 2025)
Objective: Reliable tissue adhesion to glass slides is critical for accurate histological evaluation. Egg albumen, a commonly used coating agent, often results in background staining and inconsistent performance. Aloe vera, known for its biocompatibility and adhesive properties, presents a sustainable alternative. This study aimed to develop a novel aloe vera–vinegar gel formulation and compare its slide-coating performance with that of traditional egg albumen. Methods: Fresh Aloe vera gel was extracted and combined with nonfruit vinegar, filtered, and refrigerated. Thirty paraffin-embedded tissue sections were divided into two groups: one coated with aloe vera–vinegar gel and the other coated with egg albumen. The slides were stained with hematoxylin and eosin. Two blinded observers evaluated parameters, including viscosity, adhesion, background staining, and stain intensity. The data were analysed via independent t-tests and Cohen’s kappa. Results: The viscosity (p < 0.001) and stain intensity (p = 0.002) of aloe vera–vinegar gel were significantly greater than those of egg albumen. It showed minimal background staining and consistent tissue adherence. The level of observer agreement was high across the assessments. Conclusion: Aloe vera–vinegar gel is a viable, eco-friendly alternative to egg albumen for histological slide coating. Its superior viscosity, enhanced staining characteristics, and cleaner background support its potential for routine use. Future studies should include objective physical property analyses to further validate its application.